Speciation of sulphur in asphaltenes and resins from Argentinian petroleum by using XANES spectroscopy. (15th November 2019) - Bava, Yanina B.; Geronés, Mariana; Giovanetti, Lisandro J.; Andrini, Leandro; Erben, Mauricio F.
Highlights: Sulphur K-edge XANES for Argentinian crude oils, asphaltenes and resins are presented. Sulphur moieties in the average molecular structure of asphaltenes are incorporated. The role that plays the precipitating solvent in the sulphur speciation is analyzed. Aromatic thiophene, aliphatic sulphide and disulphide groups are found in asphaltene. Sulfoxide, sulfone and sulfate moieties are present in the resin type I and II fractions. Abstract: Argentinian crude oil samples from different origins have been processed to separate in the four fractions Saturates, Aromatics, Resins, and Asphaltenes (SARA). Asphaltene and resin fractions were extracted using n- pentane and n- heptane as precipitating solvents. Sulphur contents of the samples were determined by elemental analysis and X-ray Absorption Spectroscopy at the Sulphur K-edge was used to perform sulphur speciation for resin and asphaltene fractions. Reduce sulphur as sulphides, disulphides and thiophenes dominate the spectra of asphaltenes, resins I and crude oils samples. A higher abundance of sulfoxide forms were found in the resin II fraction. In addition, it was found that the asphaltenes are more enriched in aromatic sulphur (thiophene) when the n- heptane solvent is employed. From the sulphur speciation determination it was possible to incorporate different sulphur forms in the hypothetical average molecular structures for the Argentinian asphaltenes.